STUDI IMPLEMENTASI KEBIJAKAN KAWASAN TANPA ROKOK PADA FASILITAS PELAYANAN KESEHATAN DI KABUPATEN BUNGO: FAJAR IFAN DOLLY, MAULIDA PUTRI RAHMAWATI, IKHSAN ALFARISI - Fajar Ifan Dolly Fajar (LPPM STIA Nusantara Sakti, 2020)
Various efforts to reduce the rate of active smoking in Bungo Regency and prohibit smoking activities in various places and certain public facilities are issuing local regulations on KTR. This study aims to determine and analyze the implementation of the KTR perda in health facilities, namely the puskesmas in Bungo Regency. This study uses a qualitative method approach with descriptive data. To see the success of the implementation of the KTR policy at puskesmas in Bungo District, the George Edwards III theory approach was used. For data analysis, an interactive model from Miles and Huberman was used. Data wetness used source triangulation approach. The results showed that the communication pattern of implementing the KTR perda at the health centers in Bungo Regency was carried out by socialization through a meeting chaired by the health department together with all the heads of the puskesmas. Then the message is forwarded to the entire community by the health center via verbabl and non-verbal communication. Because policy implementers do not get information directly, the implementation of the KTR perda is ideal as contained in the Ministry of Health's guidebook and the objectives of the KTR perda. The human resources for implementing the policy consist of leaders and employees appointed by the puskesmas. The budget for funds is still small in making KTR supporting facilities such as banners, stickers and there is no incentive for policy implementing employees. Full disposition from the health center and the community by providing verbal sanctions and expulsion for offenders. There is a willingness to make a Smoking Cessation Business program for smokers. Some bureaucratic structures already exist, but related to operational guidelines and technical guidelines as well as SOPs and division of tasks are still made improperly so it is necessary to conduct an evaluation by the health office of puskesmas that have not made SOP at all.